The New Forms of Social Exclusion 2019
DOI: 10.5772/intechopen.85463
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Social Exclusion: Risk in Adolescence and Old Age

Abstract: Vulnerability can be defined as the quality or state of being exposed to the possibility of being attacked or harmed, either physically or emotionally. In this chapter, it is defined as a possible ability of an individual or a group to face, manage, and anticipate a possible problem. This concept of vulnerability is associated with that of risk factor for social isolation, and therefore to situations that can also lead to illness and lack of mental and physical health. It can have its roots in poverty, in soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 45 publications
(47 reference statements)
1
29
0
3
Order By: Relevance
“…The deactivation of these areas implies a greater activation of the AI and the anterior cingulate cortex, the brain network relating to social exclusion, which is responsible for negative emotions. These results are in line with recent research (Morese et al, 2019b) about the modulation of social support on the brain area related to social exclusion. The authors found that the recruitment of TPJ modulates the negative emotions experienced during social exclusion, and when this area is deactivated by informative messages, it understands the negative social situation of exclusion, and negative emotions increase during the next negative experience.…”
Section: Suicidal Ideation and Social Exclusionsupporting
confidence: 92%
“…The deactivation of these areas implies a greater activation of the AI and the anterior cingulate cortex, the brain network relating to social exclusion, which is responsible for negative emotions. These results are in line with recent research (Morese et al, 2019b) about the modulation of social support on the brain area related to social exclusion. The authors found that the recruitment of TPJ modulates the negative emotions experienced during social exclusion, and when this area is deactivated by informative messages, it understands the negative social situation of exclusion, and negative emotions increase during the next negative experience.…”
Section: Suicidal Ideation and Social Exclusionsupporting
confidence: 92%
“…Frailty is certainly the most problematic expression of the aging population (11). It can be defined as a dynamic condition of increased vulnerability, which reflects age-related multi-systemic pathophysiological changes, associated with an increased risk of negative outcomes, such as institutionalization, hospitalization, and death (12).…”
Section: Frailtymentioning
confidence: 99%
“…Moreover, researchers found that frailty was directly associated with poorer executive function and worse sleep quality, which was also associated with worse processing speed (40). The presence of physical and/or cognitive frailty in the elderly increases the risk of negative outcomes and leads to greater use of health and care services (11).…”
Section: Frailty and Mental Healthmentioning
confidence: 99%
“…During puberty, the neurophysiological development of the prefrontal cortex occurs very quickly [1]. The prefrontal cortex deals with not only cognitive abilities such as planning and executive functions [21], but also the regulation and management of emotions.…”
Section: Social Withdrawal and Social Brainmentioning
confidence: 99%
“…Social relationships represent a very important dimension during adolescence [1]; for this reason social withdrawal is an actual phenomenon that needs to be examined in detail. As very little is known about it, the risk that may contribute to the formation of a mental health disease may be ignored.…”
Section: Introductionmentioning
confidence: 99%